Suffering, sense-making and meeting of minds: Le Chambon-sur-Lignon as literary sanctuary. (1st October 2020) - Jones, Sharon
ABSTRACT: The mapping of the relationships between space and literature finds an advocate in Bertrand Westphal who argues that the complex networks of human activity that occur in geographical locations can act as a prism for literary interpretation. This paper adopts a geocritical lens in its focus on Le Chambon-sur-Lignon and the Plateau Vivarais-Lignon, an area of France distinguished by its Protestant history and identity as a mountain retreat. It is considered in this paper as a point of confluence in time and space for three important writers: Francis Ponge (1899–1988), Albert Camus (1913–1960) and Paul Ricoeur (1913–2005). Each came to reside in Le Chambon in the 1940s and 50s because of Protestant family ties and in search of respite and recuperation. Reflections on their experiences of ill health and physical hardship (selective muteness, tuberculosis and existence as a prisoner of war), together with a consideration of their practice of writing, set the scene for a discussion of writing as medicine.